Pendampingan Pengembangan Sistem Pengarsipan di Kantor Camat Pedamaran Kabupaten Ogan Komering Ilir - Ziqrullah, Muhammad Hafiz; Kunang, Yesi Novaria; Yadi, Ilman Zuhri; afriyudi, afriyudi (Jurnal Nasional Pengabdian Masyarakat, 2024)
Archives are an essential system that must be possessed by an organization, serving as evidence, evaluation material, and planning material for future activities. Disorganized and undocumented archives in an institution will result in difficulties in searching for archives when needed. The Pedamaran Sub-district office in South Sumatera is facing challenges in rechecking archives due to the stacking of physical documents. To help address this issue, the writing team provides a solution by designing and developing a web-based archiving system. This system is organized based on categories to facilitate the input and checking of documents. After the development of the archiving system for the Pedamaran Sub-district office, further assistance is provided to ensure that officials at the Pedamaran Sub-district office can utilize the created archiving system